Kingdom of the Netherlands-Netherlands : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation highlights that the Dutch economy continues to improve, supported by exports, rising housing prices, and improving sentiment. Exports are rising on expanding global trade, but consumption remains sluggish as indebted households continue to save. The external current account surplus now exceeds 10 percent of GDP, led by an improving trade balance. Labor slack and the large output gap have pushed down core inflation, raising real interest rates. Growth is expected to reach 0.8 percent in 2014 before rising gradually to 1.2 percent in 2015, supported by rising exports and a modest recovery in housing prices. Investment is projected to remain subdued owing to weak domestic demand.